2000
DOI: 10.1002/1099-0496(200009)30:3<228::aid-ppul7>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Effect of immediate versus slow intrauterine reduction of congenital diaphragmatic hernia on lung development in the sheep: A morphometric analysis of term pulmonary structure and maturity

Abstract: The incidence of congenital diaphragmatic hernia (CDH) is 1:1,200–5,000, and the condition is associated with high mortality and morbidity attributed principally to associated pulmonary hypoplasia. One treatment approach has been for intrauterine intervention to induce lung growth to a sufficient level to allow survival at birth. Repair of the hernia in utero has been attempted, using a method of immediate reduction and repair of the hernia (patch) compared to a slow reduction method using a silastic “silo” se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Thus the diaphragmatic defects associated with CDH are a primary defect and not a secondary result of lung malformation. The concept that the lung hypoplasia is in fact secondary to the diaphragmatic defect is supported by data from the surgically induced sheep model of CDH that clearly demonstrates that a hole in the posterolateral diaphragm results in marked lung underdevelopment because of the invasion of abdominal contents and abnormal fetal breathing movements (16,17,23,25). However, there is convincing evidence demonstrating that the teratogens used in the rodent CDH model can directly interfere with lung development (1,6,13,20).…”
Section: Discussionmentioning
confidence: 99%
“…Thus the diaphragmatic defects associated with CDH are a primary defect and not a secondary result of lung malformation. The concept that the lung hypoplasia is in fact secondary to the diaphragmatic defect is supported by data from the surgically induced sheep model of CDH that clearly demonstrates that a hole in the posterolateral diaphragm results in marked lung underdevelopment because of the invasion of abdominal contents and abnormal fetal breathing movements (16,17,23,25). However, there is convincing evidence demonstrating that the teratogens used in the rodent CDH model can directly interfere with lung development (1,6,13,20).…”
Section: Discussionmentioning
confidence: 99%
“…The synergistic effects of tracheal occlusion and intrapulmonary hyperoncotic agents were studied [Kunisaki et al, 2006]. Developmental airway morphometrics in the sheep CDH model were studied, with the observation that relative hypoplasia worsened with gestational age [Lipsett et al, 2000]. Studies on nitric oxide (NO) signaling demonstrated that the NO signaling pathway is intact in the sheep CDH model [Thebaud et al, 1999a].…”
Section: Surgical Modelsmentioning
confidence: 99%
“…There have been numerous studies on the effects of repair of CDH in fetal lambs [Montgomery et al, 1995; Parsons et al, 1994]. Morphometric studies revealed differences between immediate versus slow reduction of CDH on lung development [Lipsett et al, 2000]. Liquid and partial liquid ventilation as treatment strategies were investigated [Major et al, 1995; Wilcox et al, 1995].…”
Section: Surgical Modelsmentioning
confidence: 99%
“…The lambs underwent standardized obduction, during which we first evaluated the presence of herniated viscera inside the thorax. Animals without a defect and stomach and bowel into the chest were excluded from the analysis 17 , because hypoplasia may not have been severe. The trachea and lungs were harvested, separated, and the lung‐to‐body‐weight ratio (LBWR) was calculated 18 .…”
Section: Methodsmentioning
confidence: 99%
“…We also excluded five fetuses that did not have a diaphragmatic defect at term. We did so because those animals may not have developed pulmonary hypoplasia 17 , making interpretation of the primary outcome measure (LBWR) difficult.…”
Section: Strengths and Limitationsmentioning
confidence: 99%